2013
DOI: 10.1002/jez.1800
|View full text |Cite
|
Sign up to set email alerts
|

What Do We (Need to) Know About the Melatonin in Crustaceans?

Abstract: Melatonin (N-acetyl-5-methoxy-tryptamine) was first discovered from the bovine pineal gland extract in 1958. Since then, its synthesis, metabolism, physiological, and patho-physiological functions are well studied in vertebrates; there is an increasing recognition of melatonin in invertebrates and especially in crustaceans. The presence of melatonin in crustaceans is now well documented and some functional aspects in the framework of crustacean biology have been demonstrated. This review aims at giving a compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 151 publications
(194 reference statements)
0
28
0
2
Order By: Relevance
“…In crustaceans, melatonin has been shown to have diverse physiological purposes (reviewed in [7]): Tilden et al 2003 [8] have demonstrated that melatonin modulates locomotory activity, glucose/lactate levels and neurotransmitter release in crayfish. Melatonin also has an influence on limb regeneration in the fiddler crab Uca pugilator [9] and influences the regulation of the molting of the edible crab Oziotelphusa senex senex [10].…”
Section: Introductionmentioning
confidence: 99%
“…In crustaceans, melatonin has been shown to have diverse physiological purposes (reviewed in [7]): Tilden et al 2003 [8] have demonstrated that melatonin modulates locomotory activity, glucose/lactate levels and neurotransmitter release in crayfish. Melatonin also has an influence on limb regeneration in the fiddler crab Uca pugilator [9] and influences the regulation of the molting of the edible crab Oziotelphusa senex senex [10].…”
Section: Introductionmentioning
confidence: 99%
“…This indoleamine is present in a variety of organisms, from unicellular algae to mammals, and its production follows a circadian rhythm [ 6 , 7 ]. Melatonin has also been identified in crustaceans, although its production and functions are not as well understood as they are in vertebrates [ 8 , 9 ]. Maciel and colleagues [ 10 ] reported that when the gills of the crab Neohelice granulata were incubated with melatonin (20 × 10 −9 M), oxygen consumption decreased.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers suppose that these processes could be responsible for the biological effects of geomagnetic activity [Close, 2012; Krylov, 2017; Vanderstraeten et al, 2015]. In addition, the synthesis of known mammalian circadian hormone melatonin in crustaceans also occurs in a diurnal manner and is involved in regulation of reproduction [Sainath et al, 2013]. Melatonin content in organisms directly depends on the light–dark cycle [Reiter, 1991].…”
Section: Discussionmentioning
confidence: 99%